Optimization of spray-drying process conditions for the production of maximally viable microencapsulated L. acidophilus NCIMB 701748 - Behboudi-Jobbehdar, Solmaz; Soukoulis, Christos; Yonekura, Lina; Fisk, Ian D. (Taylor & Francis, 2013)
Inrecent years, the use of spray drying for the production of anhydrobiotics has gained the interest of functional food manufacturers, mainly due to cost efficiencies and enhanced product and process flexibility (e.g., enhanced shelf life). In the present work, spray-drying conditions (air inlet temperature and feed flow rate) were optimized for the microencapsulation of the thermo sensitive probiotic lactobacilli strains Lactobacillus acidophilus stabilized in a 60:20:20 (w/w) maltodextrin: whey protein concentrate: D-glucose carrier. A 23 full-factorial experimental design was constructed with air inlet temperature (120, 140, and 160°C) and feed flow rate (6, 7.5, and 9.0 mL/min) as the independent variables and total viable counts (TVC), water activity (a w ), and cyclone recovery (CR) defined as the dependent variables. The increase in air inlet temperature from 120 to 160°C induced a significant (p < 0.001) reduction in the TVC from 9.02 to 7.20 log cfu/g, which corresponds to a97.5% loss of the L. acidophilus viable counts. On the other hand, the increase in the feed flow rate from 6 to 7.5 mL/min significantly reduced (p < 0.001) the heat-induced viability loss. A further increase in the feeding rate did not further modify the achieved thermo protection, and a detrimental impact of cyclone recovery (reduction) and water activity (increase) of the powder was observed. Using pruned quadratic mathematical models, the optimum spray-drying conditions for the production of maximally viable microencapsulated L. acidophilus were 133.34°C and 7.14 mL/min. The physicochemical and structural characteristics of the powders produced were acceptable for application with regards to residual water content, particles mean size, and thermo physical properties to ensure appropriate storage stability under room temperature conditions, with a low inactivation rate of L. acidophilus. Microcapsules appeared partially collapsed by scanning electron microscope with a spherical shape with surface concavities.